Knowledge exchange and integrated services: experiences from an integrated community intellectual (learning) disability service for adults. (25th April 2014) - Farrington, C.; Clare, I. C. H.; Holland, A. J.; Barrett, M.; Oborn, E.
Abstract Background This paper examines knowledge exchange dynamics in a specialist integrated intellectual (learning) disability service, comprising specialist healthcare provision with social care commissioning and management, and considers their significance in terms of integrated service delivery. Methods A qualitative study focusing on knowledge exchange and integrated services. Semi‐structured interviews (n = 25) were conducted with members of an integrated intellectual disability service in England regarding their perceptions of knowledge exchange within the service and the way in which knowledge exchange impinges on the operation of the integrated service. Results Exchange of 'explicit' (codifiable) knowledge between health and care management components of the service is problematic because of a lack of integrated clinical governance and related factors such as IT and care record systems and office arrangements. Team meetings and workplace interactions allowed for informal exchange of explicit and 'tacit' (non‐codifiable) knowledge, but presented challenges in terms of knowledge exchange completeness and sustainability. Conclusions Knowledge exchange processes play an important role in the functioning of integrated services incorporating health and care management components. Managers need to ensure that knowledge exchange processes facilitate both explicit and tacit knowledge exchange and do not rely excessively on informal, 'ad hoc' interactions. Research on integrated services should take account of micro‐scale knowledge exchange dynamics and relationships between social dynamics and physical factors.